Response of Black Madras Purple Rice to Pruning and Application of Unitas Super Liquid Organic Fertilizer - Jamilah, Jamilah; Haryoko, Widodo; Akriweldi, Weki (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2019)
Indonesian rice yields are still relatively low. One of the efforts to increase the yield of rice plants is to trim the foliages before flowering, in addition to the application of ‘Unitas Super’ liquid organic fertilizer (LOF). The study was carried out in the Lubuk Lintah Village, Padang City in May - September 2017. The aim of the study was to investigate the effectiveness of pruning, as a source of forage, and the concentration of ‘Unitas Super’ liquid organic fertilizer in improving rice yields. The experiment was arranged in split plot design with main plots consisting of 2 levels, namely pruning at 45 days and without pruning. The subplots consisted of 3 concentrations of ‘Unitas Super’ liquid organic fertilizer, namely 0 ml L-1, 50 ml L-1, and100 ml L-1. All treatments were replicated 3 times. Data were analyzed statistically using the F test at 5% and tested using LSD at 5%. According to the results of the observations, it can be concluded that pruning reduced the weight of 1000 seeds and panicle length, but did not reduce the yield of harvested dry grain and harvest index. Application of ‘Unitas Super’ liquid organic fertilizer did not significantly increase the growth and yield of Black Madras purple rice. The highest dry grain yield was 4.04 t ha-1 observed in plants sprayed with 50 ml L-1 ‘Unitas Super’ liquid organic fertilizer without pruning treatment.